Internal migration of physicians who graduated in Brazil between 1980 and 2014 - Mario Cesar Scheffer; Alex Jones Flores Cassenote; Aline Gil Alves Guilloux; Mario Roberto Dal Poz (BMC, 2018)
Abstract Background The internal migration of physicians from one place to another in the same country can unbalance the supply and distribution of these professionals in national health systems. In addition to economic, social and demographic issues, there are individual and professional factors associated with a physician's decision to migrate. In Brazil, there is an ongoing debate as to whether opening medicine programmes in the interior of the country can induce physicians to stay in these locations. This article examines the migration of physicians in Brazil based on the location of the medical schools from which they graduated. Methods A cross-sectional design based on secondary data of 275,801 physicians registered in the Regional Councils of Medicine (Conselhos Regionais de Medicina-CRMs) who graduated between 1980 and 2014. The evaluated outcome was migration, which was defined as moving away from the state where they completed the medicine programme to another state where they currently work or live. Results 57.3% of the physicians in the study migrated. The probability of migration ratio was greater in small grouped municipalities and lower in state capitals. 93.4% of the physicians who trained in schools located in cities with less than 100,000 inhabitants migrated. Fewer women (54.2%) migrated than men (60.0%). More than half of the physicians who graduated between 1980 and 2014 are in federative units different from the unit in which they graduated. Individual factors, such as age, gender, time of graduation and specialty, vary between the physicians who did or did not migrate. Conclusions The probability of migration ratio was greater in small municipalities of the Southeast region and strong in the states of Tocantins, Acre and Santa Catarina. New studies are recommended to deepen understanding of the factors related to the internal migration and non-migration of physicians to improve human resource for health policies.